Diseño de un sistema de costos en la fábrica de helados Skinny, parroquia Once de Noviembre ciudad de Latacunga al primer trimestre 2023 - Tello Osorio, Jessica Melisa (2024)
The purpose of this study is the design of a cost system for production orders, since it is a control tool used in this line of companies to establish the three elements of the amount involved in the production of ice cream and therefore determine the real price of their production. For the development of the enquire, compilation and investigation in different bibliographic sources was used. It should be noted that this study has a quantitative approach, since numbers and mathematical calculations were used that established the real amount of both unit and total production. It is also a descriptive, field and analytical research that provided essential information through interviews and surveys, collecting data on the elements that intervene in the final value of ice creams. With the application of the production order cost system, it was possible to identify the real price of ice cream for a production of 30,000 units in its different varieties. This is how it was specified that the production cost of flavored ice cream is $7,345.81; and its unit cost of $0.24; for ice cream of one flavor it is $6,586.87 and its unit cost is $0.25; For cone ice cream with a production of 28,000 units it is $7,499.51 and its unit cost is $0.27. On the other hand, the empirical production cost for flavored ice cream is $7,650,0000 and its unit cost is $0.25; for single flavor ice cream it is $6,850.00 and its unit cost is $0.26; and for cone ice cream it is $7,800.00 and its unit cost is $0.28. The results indicate that the differences found are remarkable. At the end of the work, it was determined that there is a 4% more investment in empirical production, due to poor management of the raw material acquisition record, calculation of labor, and indirect manufacturing values.